Hydraulic fracturing design improvements by proppant flowback mitigation method application during hydrocarbon production (Rudarsko-geološko-naftni zbornik, 2021)
Proppant flowback after hydraulic fracturing treatment is quite a serious challenge that causes damage to both downhole and surface equipment, leading to unwanted workovers and production suspension, or other negative outcomes. Some special methods including preventive as well as corrective measures already exist in the industry to overcome the proppant flowback problems. However, there is no clear guidance on how to choose the method for certain conditions, particularly during the hydraulic fracturing design stages. Therefore, the authors conducted a comprehensive review of fourteen preventive technologies to systematize them and to propose an initial decision-making approach. The following methods were considered in this paper: Resin Coated Proppants (RCP), RCP with Activator, RCP with Nanoparticles, Proppant with Liquid Resin Systems (LRS), Proppant with Surface Modification Agents (SMA), Proppant with Proppant Consolidation Aid (PCA), Cylindrical Proppant, Microfibers, Thermoset Resin Fibers, Thermoset Film Strips, Deformable Isometric Particles (DIP), Expandable Proppants, Polymer Surface Modified Proppants, and In-situ Formulated Proppants. The review reveals physical, chemical, and technological properties of each method to select criteria for effective screening. So, the reader could find the appropriate proppant flowback mitigation method corresponding to a particular reservoir and the well conditions during the initial hydraulic fracturing design stages.